The startling properties of fibroblast growth factor 2: how to exit mammalian cells without a signal peptide at hand - La Venuta, Giuseppe; Zeitler, Marcel; Steringer, Julia P.; Müller, Hans-Michael; Nickel, Walter (The journal of biological chemistry, 2015)
For a long time, protein transport into the extracellular space was believed to strictly depend on signal peptide-mediated translocation into the lumen of the endoplasmic reticulum. More recently, this view has been challenged, and the molecular mechanisms of unconventional secretory processes are beginning to emerge. Here, we focus on unconventional secretion of fibroblast growth factor 2 (FGF2), a secretory mechanism that is based upon direct protein translocation across plasma membranes. Through a combination of genome-wide RNAi screening approaches and biochemical reconstitution experiments, the basic machinery of FGF2 secretion was identified and validated.